Panduan Penulisan Laporan Ilmiah untuk Publikasi - Abdullah A Afifi (IDRIS Darulfunun Institute, 2023)
Literacy plays an important role in creating innovation. Documented phenomena and innovations will be a useful reference for developing sustainable innovations. This literacy development effort also needs to be at the academic level by providing access to writing scientifically published reports. Guidelines for writing scientific reports for publication are one way to provide access for innovators in the field to the world of academia and literacy. With these scientifically published innovation reports, efforts to develop public policies, regional innovations and public literacy have a place in the academic. This article was created so that writers can easily adjust writing reports on an academic scale. The article that is produced can become treasures for the academic world. In addition to providing technical guidelines for writing, this article also provides an overview of the publication process so that writers can better understand the scientific publishing process, which also requires a lot of time and resources.